Acid‐Resistance and Self‐Repairing Supramolecular Nanoparticle Membranes via Hydrogen‐Bonding for Sustainable Molecules Separation. Issue 23 (19th October 2021) - Han, Wang; Yin, Ming‐Jie; Zhang, Wen‐Hai; Liu, Zhi‐Jie; Wang, Naixin; Yong, Ken Tye; An, Quan‐Fu
Abstract: Functional membranes generally wear out when applying in harsh conditions such as a strong acidic environment. In this work, high acid‐resistance, long‐lasting, and low‐cost functional membranes are prepared from engineered hydrogen‐bonding and pH‐responsive supramolecular nanoparticle materials. As a proof of concept, the prepared membranes for dehydration of alcohols are utilized. The synthesized membranes have achieved a separation factor of 3000 when changing the feed solution pH from 7 to 1. No previous reports have demonstrated such unprecedentedly high‐record separation performance (pervaporation separation index is around 1.1 × 10 7 g m −2 h −1 ). More importantly, the engineered smart membrane possesses fast self‐repairing ability (48 h) that is inherited from the dynamic hydrogen bonds between the hydroxyl groups of polyacrylic acid and carbonyl groups of polyvinylpyrrolidone. To this end, the designed supramolecular materials offer the membrane community a new material type for preparing high acid resistance and long‐lasting membranes for harsh environmental cleaning applications. Abstract : Size‐tunable hydrogen‐bond supramolecular nanoparticles are synthesized for separation membrane fabrication, which can work stably at pH = 1 condition and exhibit self‐repairing ability.